Long-term Chikungunya sequelae and quality of life 2.5 years post-acute disease in a prospective cohort in Curaçao - Churnalisa Doran; Jelte Elsinga; Ante Fokkema; Kevin Berenschot; Izzy Gerstenbluth; Ashley Duits; Norediz Lourents; Yaskara Halabi; Johannes Burgerhof; Ajay Bailey; Adriana Tami (Public Library of Science (PLoS), 2022)
Background Little is known about the persistence and impact of non-rheumatic symptoms after acute chikungunya disease. We have studied the clinical presentation and long-term impact of rheumatic and non-rheumatic symptoms on health related quality of life (QoL) 2.5 years after disease onset. Additionally, the validity of the Curaçao Long-Term Chikungunya Sequelae (CLTCS) score in classifying disease severity over time was evaluated. Methodology/Principal findings This prospective cohort study followed 248 chikungunya patients. Symptoms and SF-36 QoL were evaluated during baseline and follow-up at 2.5 years using questionnaires. Chikungunya disease status was classified using the CLTCS-score. At 2.5 years after disease onset patients were classified as being recovered (43%), mildly (35%) or highly (22%) affected. In comparison to mildly affected, highly affected patients reported the highest prevalence of ongoing rheumatic and non-rheumatic/psychological symptoms, with increased prevalence of arthralgia in the lower extremities (p = .01) and fatigue (p = .049) over time, and higher pain intensity (p < .001). Compared to mildly affected, being highly affected was associated with weakness in the lower extremities (OR: 1.90; CI: 1.29-2.80, p = .001) and worsened physical and mental QoL impairment. Conclusions Patients are both physically and psychologically affected by rheumatic and non-rheumatic symptoms of long-term chikungunya disease. The CLTCS-score is an easy to use instrument for classifying long-term chikungunya disease severity and impact and can facilitate health care providers in identifying highly affected patients who are prone to develop severe QoL impairment. Highly affected patients are recommended to be treated in a multidisciplinary setting to improve physical and psychological functioning, and QoL. Author summary Chikungunya disease manifestation is characterized by a sudden onset of non-rheumatic flu-like symptoms and debilitating rheumatic symptoms in the acute phase. Little is known about the persistence of non-rheumatic symptoms after acute disease. In this prospective cohort study we investigated the clinical manifestations and persistence of baseline rheumatic and non-rheumatic/psychological symptoms and their impact on health related quality of life (QoL) 2.5 years after disease onset. Moreover, we investigated the performance of the classification instrument the Curaçao Long-Term Chikungunya Sequelae (CLTCS) score in classifying chikungunya disease severity over time. We found that 57% of the patients were still affected 2.5 years after disease onset. An increase of mainly recurrent rheumatic and non-rheumatic/psychological symptoms including fatigue, insomnia, sombreness, and loss of vitality were reported, with a significantly higher symptom recurrence and pain intensity reported by highly affected patients. In addition, QoL assessment indicates that the disease burden impaired the physiological well-being of these patients. We also showed that the CLTCS-score can be used to easily identify highly affected patients. This study demonstrates that disease severity increases non-rheumatic symptoms and subsequent physiological impairments and suggests a multidisciplinary treatment approach to treat the psychological effects of long-term chikungunya disease.